Pengaruh protein dan enzim papain dalam pakan isokalori terhadap efisiensi pemanfaatan pakan dan pertumbuhan ikan patin (Pangasius hypopthalmus) - Makmuri Makmuri; Subandiyono Subandiyono; Ristiawan Agung Nugroho (Departemen Akuakultur FPIK UNDIP, 2022)
ABSTRACTCatfish (Pangasius hypopthalmus) is one of the high economically freshwater fish. There are problems in catfish culture, especially related to the low of feed utilization. This could be solved by addition of protein and papain enzyme in feeds which play an important role on protein synthesis, so that it helps increasing the fish growth. The aim of the research was to analyze the effect of protein and papain enzyme in isocaloric feeds on the feed utilization efficiency and growth of catfish (P. hypopthalmus). The research was conducted in Mei to June 2018, at the Teaching Factory, Diponegoro University, Semarang. The body length of trial fish used ranged between 7 to 9 cm. The experimental method applied was factorial randomized design with two factors (order 2 x 2). Each factor consisted of two treatment levels with 3 replicates, so that, 12 experimental units were required. The first factor was feed with protein of 26% (A1) and 32% (A2), while the second factor was feed with the addition of papain enzyme as much as 0,25 g/kg feed (B1) and 0,50 g/kg feed (B2), respectively. Results showed that combination of protein and papain in an isocaloric feed had a significant effect on the total of feeding consumption level (TFC), feed utilization efficiency (FUE), and relative growth rate (RGR), but had no significant effect on the survival rate (SR). Results showed that the optimum dose of protein and papain in isocaloric feed was 32% of protein dan 0,25 g of papain/kg feed which was able to produced TFC of 154,32±4,52 g, FUE of 58,35±2,80%, and RGR of 4,66±0,06%/day.Keywords: Catfish, Protein, Papain Enzyme, Isocaloric Feed, Growth